2019
DOI: 10.17533/udea.redin.20191258
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of nasgro equation for mixed-mode loading using experimental and numerical data

Abstract: A procedure to calibrate the NASGRO equation in a high yield-strength steel under mixed-mode loading (I + II) is presented. The calibration consists in obtaining the material parameters known as C, m, p and q. The procedure is based on experimental and numerical results. The experimental tests were used to characterize the material and obtain fatigue crack growth data. For the fatigue tests, tapered double cantilever beam (TDCB) specimens with different maximum load and load ratio values were used. Through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…This means that a crack grows under fatigue loading if ∆Keq exceeds the fatigue threshold (∆Kth), or the crack grows under static loading when the equivalent SIF (Keq) exceeds the fracture toughness (Kc), as has been postulated before [16]. Finally, we can say that SENT samples have gained popularity in testing pipelines [18] and welds or offer less restriction [6,19], and C(T) samples offer a larger space to observe CP evolution [20][21][22]. Lately, some researchers have devoted efforts to evaluating CP in complex problems using artificial intelligence, such as heterogeneous materials [7], metamaterials [23], or composites [24].…”
Section: Introductionmentioning
confidence: 99%
“…This means that a crack grows under fatigue loading if ∆Keq exceeds the fatigue threshold (∆Kth), or the crack grows under static loading when the equivalent SIF (Keq) exceeds the fracture toughness (Kc), as has been postulated before [16]. Finally, we can say that SENT samples have gained popularity in testing pipelines [18] and welds or offer less restriction [6,19], and C(T) samples offer a larger space to observe CP evolution [20][21][22]. Lately, some researchers have devoted efforts to evaluating CP in complex problems using artificial intelligence, such as heterogeneous materials [7], metamaterials [23], or composites [24].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, numerical studies [12] investigated the effects of mode-mixity in surface cracks, observing a difference in crack growth rate under mixed modes in steel. Moreover, Berrios-Barcena et al [13] reproduced FCG in a double cantilever sample of low-carbon steel. Further research by Dirik and T. Yalçinkaya [14] tested the Tanaka model against numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Here is where the models to quantify the combination of SIF under mixed modes come into play [5]. Moreover, FCG is usually conducted using analytical methods for simple loading cases, numerical methods [12][13][14], a combination of both, or even with non-parametric models [22]. A review of some of them can be found in [23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, FCG is usually conducted using analytical methods for simple loading cases, numerical methods [11], [12], [13], a combination of both, or even with non-parametric models [21]. A review of some of them can be found in [22].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, numerical studies [11] investigated the effects of mode-mixity of surface cracks, observing a difference in crack growth rate under mixed mode in steel. Moreover, [12] reproduced FCG in a double cantilever sample of low-Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s). MDPI and/or the editor(s) disclaim responsibility for any injury to people or property resulting from any ideas, methods, instructions, or products referred to in the content.…”
mentioning
confidence: 99%